Initial evaluation of the Celesteion large-bore PET/CT scanner in accordance with the NEMA NU2-2012 standard and the Japanese guideline for oncology FDG PET/CT data acquisition protocol version 2.0 - Kaneta, Tomohiro (EJNMMI Res, 2017)
BACKGROUND: The goal of this study was to evaluate the performance of the Celesteion positron emission tomography/computed tomography (PET/CT) scanner, which is characterized by a large-bore and time-of-flight (TOF) function, in accordance with the NEMA NU-2 2012 standard and version 2.0 of the Japanese guideline for oncology fluorodeoxyglucose PET/CT data acquisition protocol. Spatial resolution, sensitivity, count rate characteristic, scatter fraction, energy resolution, TOF timing resolution, and image quality were evaluated according to the NEMA NU-2 2012 standard. Phantom experiments were performed using (18)F-solution and an IEC body phantom of the type described in the NEMA NU-2 2012 standard. The minimum scanning time required for the detection of a 10-mm hot sphere with a 4:1 target-to-background ratio, the phantom noise equivalent count (NEC(phantom)), % background variability (N (10mm)), % contrast (Q (H,10mm)), and recovery coefficient (RC) were calculated according to the Japanese guideline. RESULTS: The measured spatial resolution ranged from 4.5- to 5-mm full width at half maximum (FWHM). The sensitivity and scatter fraction were 3.8 cps/kBq and 37.3%, respectively. The peak noise-equivalent count rate was 70 kcps in the presence of 29.6 kBq mL(−1) in the phantom. The system energy resolution was 12.4% and the TOF timing resolution was 411 ps at FWHM. Minimum scanning times of 2, 7, 6, and 2 min per bed position, respectively, are recommended for visual score, noise-equivalent count (NEC)(phantom), N (10mm), and the Q (H,10mm) to N (10mm) ratio (QNR) by the Japanese guideline. The RC of a 10-mm-diameter sphere was 0.49, which exceeded the minimum recommended value. CONCLUSIONS: The Celesteion large-bore PET/CT system had low sensitivity and NEC, but good spatial and time resolution when compared to other PET/CT scanners. The QNR met the recommended values of the Japanese guideline even at 2 min. The Celesteion is therefore thought to provide acceptable image quality with 2 min/bed position acquisition, which is the most common scan protocol in Japan.